2018
DOI: 10.18805/ijare.a-4905
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-physiological and oxidative responses of nitrogen and phosphorus deficiency in wheat (Triticum aestivum L.)

Abstract: Wheat is one of the most important cereal crops in India.Nitrogenand phosphorus arethe major nutrients, which are deficient in Indian soil; hence the effectsof this deficiency on morpho-physiological response and antioxidant metabolism were studied in wheat to improve the knowledge and understanding of adaptive responses of plants.Two wheat genotypes WH1080 and WH1105 were raised hydroponically for 15 and 25 days, using germination paper with four treatments- T1(0%N+0%P), T2(0%N+100%P), T3(100%N+0%P), T4(100%N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(26 reference statements)
3
1
0
Order By: Relevance
“…Therefore, SOD is important for tolerating P stress and could be considered essential for mycorrhizal colonization of maize plants grown in calcareous soil. These results corroborate the observations of Singh et al (2018), who found enhanced SOD activity under P deficiency in wheat (Triticum aestivum L.) cultures. Singh (2015) reported that SOD activity in non-mycorrhizal tomato plants was higher than in mycorrhizal plants cultivated under appropriate water levels.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, SOD is important for tolerating P stress and could be considered essential for mycorrhizal colonization of maize plants grown in calcareous soil. These results corroborate the observations of Singh et al (2018), who found enhanced SOD activity under P deficiency in wheat (Triticum aestivum L.) cultures. Singh (2015) reported that SOD activity in non-mycorrhizal tomato plants was higher than in mycorrhizal plants cultivated under appropriate water levels.…”
Section: Discussionsupporting
confidence: 92%
“…The crosses of Vishal x Vijay and ICC 4958 x Vijay recorded less increase in lipid peroxidation rate of 27.68 and 27.88 percent, respectively (Fig 2A). The increase in leaf MDA contents observed under drought stress are consistent with Singh et al (2018) in wheat. In the present study, increased levels of ROS were found under drought stress in chickpea parents and their crosses, as indicated by increased lipid peroxidation rate.…”
Section: Resultssupporting
confidence: 81%
“…In this study, the most noticeable impact on the measured biochemical parameters in wheat spikes had a low nitrogen level itself. Various abiotic stress conditions lead to the overproduction of ROS and imbalanced ROS detoxification, which lead to lipid peroxidation [8,30]. The present study provided similar results, in which low nitrogen level as an abiotic stress factor caused an increase in lipid peroxidation in most varieties.…”
Section: Discussionsupporting
confidence: 81%